2017
DOI: 10.1002/14651858.cd007419.pub5
|View full text |Cite
|
Sign up to set email alerts
|

Anti-vascular endothelial growth factor for diabetic macular oedema: a network meta-analysis

Abstract: Anti-VEGF drugs are effective at improving vision in people with DMO with three to four in every 10 people likely to experience an improvement of 3 or more lines VA at one year. There is moderate-certainty evidence that aflibercept confers some advantage over ranibizumab and bevacizumab in people with DMO at one year in visual and anatomic terms. Relative effects among anti-VEGF drugs at two years are less well known, since most studies were short term. Evidence from RCTs may not apply to real-world practice, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
96
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 150 publications
(112 citation statements)
references
References 103 publications
5
96
0
4
Order By: Relevance
“…However, ranibizumab and bevacizumab did not show significant differences [ 28 , 33 ]. A previous meta-analysis study also confirmed that bevacizumab and ranibizumab did not differ in terms of BCVA, but ranibizumab was more effective in terms of CST reduction with a low-certainty of evidence [ 43 ]. To reinforce the validity of our meta-analysis, clinical trials comparing the 3 anti-VEGF agents with the DEX implant as well as extended follow-up trials should be conducted in the future.…”
Section: Discussionmentioning
confidence: 79%
“…However, ranibizumab and bevacizumab did not show significant differences [ 28 , 33 ]. A previous meta-analysis study also confirmed that bevacizumab and ranibizumab did not differ in terms of BCVA, but ranibizumab was more effective in terms of CST reduction with a low-certainty of evidence [ 43 ]. To reinforce the validity of our meta-analysis, clinical trials comparing the 3 anti-VEGF agents with the DEX implant as well as extended follow-up trials should be conducted in the future.…”
Section: Discussionmentioning
confidence: 79%
“…This might be a reflection of under treatment and reduced follow-up, specifically in treatment-naïve patients, which is reflective of any real-world evidence study. However, this gap appeared to be less in mCNV than in nAMD and DME studies [31,32]. This could also be due to the possibility that patients with mCNV are comparatively younger than patients with nAMD and DME and are more likely to notice any changes in their VA or distortion.…”
Section: Discussionmentioning
confidence: 90%
“…No differences in overall safety between the three antiangiogenic drugs that are currently available but results are imprecise for cardiovascular events and death [ 38 ]. Therefore, storage of antiangiogenics within cells of intraocular tissues as observed in vivo after intravitreal injection into monkey eyes, may result in unknown side effects during long-term treatment of patients.…”
Section: Discussionmentioning
confidence: 99%